NEW GATEWAY TO IDENTIFICATION, PALATAL RUGAE - Imran Jawaad; Farah Waseem; Durdana Zafar; Shahzad Waheed Qureshi; Gulrez Amin; Shazia Omer (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Identification is one of the most important criteria among living and dead humans and is the forefront of all medicolegal cases. Even with advanced technology and latest gadgets it is considered to be a problematic area for forensic personals. Multiple tools are in vogue which individually and majority of times collectively are used to resolve the problem of identification especially in cases when the person is unknown or in case of death when whole corpse is not available. Conventionally, dactylography, anthropometry and some other traditional methods of identification are in use, a very simple, cost effective and reliable method to add in the list is palatal rugae. When used with other methods of identification it becomes highly effective and helps to resolve almost impossible cases as it is unique to each person and will remain as such throughout the life of a person.